Identifikasi Lalat Buah yang Menyerang Buah Naga (Hylocereus sp.) di Kecamatan Batu Ampar, Kabupaten Tanah Laut Kalimantan Selatan - Pramudi, Muhammad Indar; Rosa, Helda Orbani (Universitas Muhammadiyah Yogyakarta, 2016)
Identification of fruit flies of dragon fruit in Tanah Laut has never been conducted. This research was aimed to identify fruit flies species of dragon fruit and its natural enemies in Batu Ampar, Tanah Laut, Kalimantan Selatan. The fruit flies attacking dragon fruit in the field was collected. Observation was performed on the development of the larvae until adult and finally emerging adult was identified as well as its parasitoid. The result showed that the obtained fruit flies was Bactrocera dorsalis Hendel and Aceratoneuro myiaindica (Hymenoptera: Eulophidae: Tetrastichinae) was found as the parasitoid. Five predators was found as its natural enemies, namely red ants (Hymenoptera: Formicidae: Solenopsis), rangrang ant (Hymenoptera: Formicidae: Oecophylla), spiders (Arachnida), kumbang stafilinid (Coleoptera: Staphylinidae: Paederinae) and earwig (Dermaptera: Forficulidae: Forficula).